Implementation of Learning in the Covid 19 Era Grade III Study at Elementary School: Penerapan Pembelajaran di Era Covid 19 Studi Kelas III SD - Aniyah Hidayah; Rifki Afandi (Academia Open, 2022)
This study aims to describe the learning of elementary school teachers in implementing learning from the Covid-19 pandemic and inhibiting factors for teachers in implementing bold learning. The research method uses descriptive qualitative research. The research subjects were teachers and third-grade students of Elementary School Plaosan II Wonoayu, while the research data collection techniques used observation, documentation and interviews. Analysis of research data using the Miles and Hiberman analysis data model. The research shows that parents have a role, including learning planning carried out by teachers in bold learning such as syllabus, learning implementation and learning media by making their own and conducting discussions with other teachers. Teachers have not experienced and mastered learning technology, so it is challenging to design bold activities.